2021
DOI: 10.17430/jhs.2021.11.1.7
|View full text |Cite
|
Sign up to set email alerts
|

Auditory Evaluation in a Case of Hearing Loss in an Infant With Congenital Zika Syndrome (Czs)

Abstract: Background:The Zika virus (ZIKV) was detected in Brazil in 2014. At the end of 2015 microcephaly was the first distinctive sign. By 2016, the first two cases of congenital Zika had been described, with a strong correlation between the virus and microcephaly.Case report: A male infant was born at 32 weeks gestation, weight 1,750 grams, cranial perimeter 26 cm. He remained in intensive care for 5 days for neonatal seizures, required oxygen therapy, and had early sepsis. After 11 days in hospital a diagnosis of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
0
1
0
1
Order By: Relevance
“…Testes audiológicos tem mostrado alterações cocleares. sincronia de tronco encefálico dentro da normalidade e alterações em testes que avaliam funções corticais essenciais para o desenvolvimento de linguagem [37][38][39] . Estudo que avaliou 88 crianças infectadas pelo ZIKV com limiares auditivos normais.…”
Section: Discussionunclassified
“…Testes audiológicos tem mostrado alterações cocleares. sincronia de tronco encefálico dentro da normalidade e alterações em testes que avaliam funções corticais essenciais para o desenvolvimento de linguagem [37][38][39] . Estudo que avaliou 88 crianças infectadas pelo ZIKV com limiares auditivos normais.…”
Section: Discussionunclassified
“…Audiological tests have shown cochlear disorders. brainstem synchrony within the normal range and alterations in tests that assess essential cortical functions for language development [37][38][39] . A study that assessed 88 children infected by ZIKV with normal hearing thresholds found delayed development of communication skills in 87.5% of the sample.…”
Section: Discussionmentioning
confidence: 99%
“…And that the hearing loss seems to be present at birth and no change or worsening of the auditory condition has been observed. A study 13 documented a scenario of hearing impairment in an infant afflicted with CZS, who spent five days in intensive care due to neonatal seizures, necessitating oxygen therapy, and experienced early sepsis. Additionally, following an 11-day hospital stay, a diagnosis of microcephaly was established, and at the age of 12 months, computed tomography revealed hydrocephalus, accompanied by calcifications in the subcortical region, basal nuclei, cerebellum, and brainstem.…”
Section: Introductionmentioning
confidence: 99%